BAHAN AJAR ALAT PERMAINAN EDUKATIF (APE) BERBASIS KARAKTER BAGI MAHASISWA PRODI PKAUD IAKN AMBON - Mercy F Halamury (TANGKOLEH PUTAI, 2021)
This research was conducted at the PKAUD study program, Faculty of Christian Education (FIPK) IAKN AMBON, with the aim of developing character values ??through teaching materials in the Educational Game Tools (APE) course. The implementation of character education through the Educational Game Tool (APE) course is in addition to making students master the targeted competencies (materials), it is also designed to make students recognize, realize / care about life values ??that make them able to behave well by showing the character of responsibility. , communicative and creative. The integration of character education in the learning process is carried out starting from the planning, implementation (presenting), practice and evaluation stages of learning. From the data obtained in this study, it shows that with the teaching materials of educational game tools in the types of APE, the characters expected from within students through APE practice activities, namely the character of responsibility, creative character and communicative character can be said to appear 75%. at each stage for four meetings